Effects of mining activities on the distribution, controlling factors, and sources of metals in soils from the Xikuangshan South Mine, Hunan Province. (23rd September 2021) - Xie, Qing; Ren, Bozhi; Hursthouse, Andrew; Shi, Xiyang
Abstract: In this study, we analyzed 53 topsoil samples from the Xikuangshan South Mine in Hunan Province to investigate the distribution characteristics of pH and the concentrations of selected metals to determine the controlling factors and identify their sources. Kriging interpolation, correlation analysis, principal component analysis, the index of the geoaccumulation index, and Hakanson's potential ecological risk were applied. The results show that the mean values of Pb, As, Cd, and Sb in the study area were larger than the background value of mountain soil in Hunan Province, and only the average Cr concentration was slightly lower than the background value. The spatial distributions of pH and five metals in the soil were very different, indicating that pH had no significant effect on the distribution of the metals. The wind, rivers, and land‐use patterns in different regions of the study area may be the main reasons for their distribution patterns. The correlation component and principal component analysis revealed that Pb showed positive correlations with Cr and Cd, respectively, and Sb‐As and Cr‐Cd showed strong paired correlations. The cumulative proportion of the first two components accounted for 70.516% of the total variance, which suggests that mining activities are a major source of As and Sb, whereas Pb, Cr, and Cd were derived from natural and anthropogenic sources. The geoaccumulation index revealed that the major pollutants in the soils were mainly Cd, followed by Sb and As. The soils in the study area were moderately contaminated with Pb and lightly polluted by Cr. The ecological hazards of each metal in descending order were Cd > Sb > As > Pb > Cr. The index of the comprehensive potential ecological risk for metals indicated that the Xikuangshan South Mine is at or above a moderate ecological risk level, with an extremely strong potential for ecological risks posed by Cd and Sb. Integr Environ Assess Manag 2022;18:748–756. © 2021 SETAC Key Points: The mean values of Pb, As, Cd and Sb in the Xikuangshan South Mine are over the background value of mountain soil in Hunan Province, only the average Cr content is slightly lower than the background value. pH had no significant effect on the spatial distribution of metals, the wind, rivers and land use patterns in different regions may be the main reasons for their distinguishing distribution patterns. The cumulative proportion of the first two components suggest mining activities were the major sources for As and Sb, natural and anthropogenic sources for Pb, Cr and Cd. The index of comprehensive potential ecological risk for metals indicated that the Xikuangshan South Mine was at or above the level of moderate ecological risk, with an extremely strong potential for the ecological risks pose by Cd and Sb.